Uterine Natural Killer Cell Heterogeneity: Lessons From Mouse Models - Sojka, Dorothy K. (Frontiers in Immunology, 2020)
Natural killer (NK) cells are the most abundant lymphocytes at the maternal-fetal interface. Epidemiological data implicate NK cells in human pregnancy outcomes. Discoveries using mouse NK cells have guided subsequent advances in human NK cell biology. However, it remains challenging to identify mouse and human uterine NK (uNK) cell function(s) because of the dynamic changes in the systemic-endocrinological and local uterine structural microenvironments during pregnancy. This review discusses functional similarities and differences between mouse and human NK cells at the maternal-fetal interface.